2016
DOI: 10.4018/ijgbl.2016010101
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking in Constructionist Video Games

Abstract: Video games offer an exciting opportunity for learners to engage in computational thinking in informal contexts. This paper describes a genre of learning environments called constructionist video games that are especially well suited for developing learners' computational thinking skills. These games blend features of conventional video games with learning and design theory from the constructionist tradition, making the construction of in-game artifacts the core activity of gameplay. Along with defining the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 49 publications
2
30
0
2
Order By: Relevance
“…Digital games proved attractive and engaging for all groups of people and therefore, Game-Based Learning (GBL) has been proposed as one pedagogical framework for developing CT skills [62]. In order to help to acquire CT skills two main approaches have been introduced in GBL: learning through designing games and learning through gameplay.…”
Section: Game-based Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital games proved attractive and engaging for all groups of people and therefore, Game-Based Learning (GBL) has been proposed as one pedagogical framework for developing CT skills [62]. In order to help to acquire CT skills two main approaches have been introduced in GBL: learning through designing games and learning through gameplay.…”
Section: Game-based Learningmentioning
confidence: 99%
“…In line with [30], TAPASPlay also aims to foster collaborative learning, that is, it regards CT as a creative and social practice. Finally, TAPASPlay fits within the realm of Constructionist Video Games [62], namely computational environments in which players may create personally meaningful artifacts to overcome artificial conflicts or obstacles resulting in quantifiable outcomes. In the following, the design and implementation of TAPASPlay are described in detail.…”
Section: Learning Through Gameplaymentioning
confidence: 99%
“…The main findings of the reviewed studies primarily included findings about CT skills. Study findings included elements that improved CT skills such as programming instruction (Olabe et al, 2015;Pellas & Peroutseas, 2016;Perez & Roig-Vila, 2015;Repenning et al, 2014;Wang, Wang, & Liu, 2014), robotics (Bers, 2010;Sullivan & Heffernan, 2016) and computer programs (Ioannidou, Repenning, & Webb, 2009;MorenoLeón, Robles, & Román-González, 2015;Repenning et al, 2015;Weintrop et al, 2016). It was observed that these studies were conducted since the beginning of the related literature.…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…Accordingly, it was observed that several topics such as programming instruction (Denner, Werner, Campe, & Ortiz, 2014;Pellas & Peroutseas, 2016), computer software (Haseski, İlic, & Tugtekin, 2017;Tahy, 2016;Weintrop, Holbert, Horn, & Wilensky, 2016) and robots (Berland & Wilensky, 2015;Bers, 2010;Kafai & Burke, 2013) were investigated with respect to CT. Furthermore, there are also studies in the literature on the integration of CT to educational contexts (Israel, Pearson, Tapia, Wherfel, & Reese, 2015;Olabe, Basogain, & Basogain, 2015) and the design of CT-oriented curricula (Bers, Flannery, Kazakoff & Sullivan, 2014;Manson & Olsen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Others have found that learning in games may have more to do with the surrounding physical and social environment than the design of the game itself (Stevens et al, 2008). Many studies rely on testing learning technologies in controlled, laboratory conditions (Weintrop et al, 2016) and fail to consider the real world contexts in which these technologies are deployed (Sanford et al, 2015;Stevens et al, 2008;Wright and Parachoma, 2011). Research is also limited by what researchers choose to study.…”
Section: Introductionmentioning
confidence: 99%